2012
DOI: 10.1097/hjh.0b013e32835527ae
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of central blood pressure and arterial stiffness

Abstract: Central systolic and PPs, brachial PP, AIx, aortic PWV are moderately heritable. A moderate genetic covariance among aortic PWV and central PP, central SBP and brachial SBP was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
4
41
1
1
Order By: Relevance
“…Variations in SBP and DBP were primarily explained by additive genetic factors, accounting for 61% and 58% of their total variances, with residual variances explained by unique environmental factors, which was consistent with previous studies (Jermendy et al, 2011;Wu et al, 2011). Although low-modest heritability has been estimated in many different ethnic populations (Bochud et al, 2005;DeStefano et al, 2004;Tarnoki et al, 2012), our heritability estimate of PP (0.42) is close to a recent study reported by Tarnoki et al (2013) in Italian, Hungarian, and American twins, reflecting that maybe the heritability of PP does not vary considerably by race. Second, there were significant pair-wise phenotypic correlations among PP, SBP, DBP, and BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Variations in SBP and DBP were primarily explained by additive genetic factors, accounting for 61% and 58% of their total variances, with residual variances explained by unique environmental factors, which was consistent with previous studies (Jermendy et al, 2011;Wu et al, 2011). Although low-modest heritability has been estimated in many different ethnic populations (Bochud et al, 2005;DeStefano et al, 2004;Tarnoki et al, 2012), our heritability estimate of PP (0.42) is close to a recent study reported by Tarnoki et al (2013) in Italian, Hungarian, and American twins, reflecting that maybe the heritability of PP does not vary considerably by race. Second, there were significant pair-wise phenotypic correlations among PP, SBP, DBP, and BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Our study provided evidence that genetic factors did not substantially contribute to this phenomenon, however, diverse environmental factors (eg, lifestyle: cigarette smoking, nutrition, lack of physical exercises) had a tremendous influence (70%). Our study is in accordance with previous findings that parenchymal thickness was a good marker of atherosclerotic renal disease, considering that atherosclerotic phenotypes were also mainly influenced by environmental factors (23)(24)(25)(26)(27). On the basis of such results, we believe that RPT should be monitored as an important risk factor in individuals with an unhealthy lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…73,74 In a study of 1480 individuals belonging to 817 nuclei of the Framingham Study Offspring Cohort, Mitchell et al 75 demonstrated that the heritability of PWV was 40%. In another study involving pairs of dizygotic and monozygotic twins living in Hungary and the United States, Tarnoki et al 76 observed 51%, adjusted for age, gender and country of origin. A study of 930 individuals in the family of the Erasmus Rucphen Family Study (SayedTabatabaei et al 77 ) found that the heritability of PWV was 26%, adjusted for several risk factors (gender, age, mean arterial pressure, LDL-c , heart rate, and fasting glycemia).…”
Section: Genetic Aspects Of Arterial Stiffness Heritability Of Arterimentioning
confidence: 96%